Bayan Tafsir - Muhammad Zaini (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2013)
Many verses of the Qur’an having general meanings indicate that it is a  global holy book which covers all aspects of life. It is a God’s mercy to all  mankind in the universe. In fact, the verses of the Qur’an having generl meanings  have been explained by the Qur’an itself because one verse explains another  verse, yufassiru ba`dhuhu ba’dhan. This means the general meaning verses are  not contradictory one to each other that during the Prophet time, Rasulullah peace  be upon him explained the meanings of the Qur’an and applied it in his daily life  together with his companions. In this context, the Prophet functions as the  mubayyin (explainer) of the Qur’an either in his sayings, actions or permissions.